IDENTIFICATION BUILDINGS FUNCTION OF CENTRAL T-SHIRT INDUSTRY IN SURAPATI STREET CORRIDOR, BANDUNG CITY - Karto Wijaya; Amat Rahmat; Fani Sukma Amalia (Universitas Kebangsaan Republik Indonesia [UKRI], 2019)
ABSTRACT : Population growth in the city of Bandung is increasing so that the laha needs especially commercial activities are also increasing both in the city center to the suburbs including Cibeunying Kaler District, Bandung City. The development of this commercial activity also occurs along the Surapati road corridor, especially those in Cibeunying Kaler District. Surapati road corridor is designated as a holy shirt tourism area with the existence of outlets as the main activity. The existence of this corridor also has various supporting activities such as economic/trade, social, health, worship, education and government building activities. With a variety of activities in it, so that it can lead to changes in residential functions into commercial buildings, such as changes in land use from settlements to an outlet area for t-shirts, trade and services for trade and service activities following market guidelines. This study aims to identify the functions of trade buildings along the Surapati road corridor in Bandung City. By using a qualitative descriptive method to determine the effect of any factors that influence changes in function in the corridor of Bandung city, Surapati. While the factors that influence the change are social factors, economic factors, accessibility, factors, and adequate infrastructure facilities around the Surapati road area Keywords : Changes in Land Function, Commercial Activities, Corridors